Methane concentration in Allan Hills ice cores - Bender, Michael; Brook, Edward J; Higgins, John; Yan, Yuzhen (IEDA: US Antarctic Program Data Center, 2019)
Abstract: This file includes the concentration methane (CH4) in Allan Hills ice cores (ALHIC1502 and ALHIC1503).